Skills and qualifications for the special library environment in Jamaica: a job advertisement analysis. Issue 1 (3rd February 2021) - Robinson, Marsha-Gay
Abstract : Purpose: The purpose of this article is to examine what employers seek when recruiting library and information professionals for a special library environment in Jamaica. Design/methodology/approach: A content analysis of a sample of 47 advertisements for information professionals in a special library environment in Jamaica from 2013 to 2019 was collected. Findings: The findings indicated that a variety of professional, generic and personal attributes were in demand for these professionals. There was a strong emphasis on advanced computer skills as well as communication and interpersonal skills. Research limitations/implications: While job advertisements offer some insight into skills requirements and qualifications for employment, it may not reflect the actual person employed. Practical implications: This paper will provide useful information for library school educators, existing information professionals and those interested in entering the field as it provides an overview of the skills and requirements for jobs in the special library environment in Jamaica. Originality/value: Despite there being a plethora of job advertisements studies in librarianship, few studies examine advertisements for information professionals in a special library environment. To the best of the author's knowledge, there is no study focusing on Jamaica.